Exploring the Cultural Customs of Mandi Belimau: Insights from Young People and Parents in 4 Belui Villages - Suci Osmoga Dewi; Isti Komarni; Dhiauddin (The Progress: Journal of Language and Ethnicity, 2023)
The Belimau bath is a significant cultural custom observed among the Malay community, specifically in the four Belui villages, which will be discussed in detail. This traditional practice has been passed down through generations, dating back to ancient times and the era of our ancestors. Typically performed during the month of Safar, the Belimau bath serves as a means of washing and purifying heirlooms found in the four Belui villages. The bath involves mixing regular water or bathing water with the juice of kaffir lime, key orange, and other ingredients. According to the village elders, the Belimau bath holds symbolic significance as it is believed to reject negative influences, promote self-purification, and foster mental well-being. On the other hand, the youth in the four Belui villages perceive the Belimau bath as a means to honor and uphold the cultural customs of their ancestors. Despite the passage of time, the young generation in these villages continues to practice the Belimau bath, not only to pay homage to their ancient traditions but also to experience its refreshing effects on the body.